AVALIACAO DO EFEITO DO VENENO DE APIS MELLIFERA EM CULTURAS DE E. COLI, S. TYPHIMURIUM E Y. ENTEROCOLITICA TRATADAS COM BLEOMICINA - Varanda, Eliana Aparecida [UNESP] (My University, 1995)
Apis mellifera bee venom (Africanized honey bee) was tested for the ability to protect against the lethal effect of bleomycin, an antibiotic and antineoplastic agent. Since the radioprotective effect of the venom has been observed on the other biological systems, in the present study the venom was applied to cultures of enterobacteria treated with bleomycin, a radiomimetic agent. The venom did not act as a protective agent against bleomycin in E. coli, S. typhimurium or Y. enterocolitica.
Evaluation of the effect of Apis mellifera bee venom in E. coli, S. typhimurium and Y. enterocolitica culture bleomycin-treated
Keywords: Apis mellifera bee venom; bleomycin; enterobacterias; antibiotic agent; antineoplastic agent; bee venom; radioprotective agent; controlled study; cytotoxicity; enterobacteriaceae; escherichia coli; nonhuman; salmonella typhimurium; yersinia enterocolitica